Wirtschaftsdeutsch in der universitären Ausbildung im Fach Germanistik in Polen – Versuch einer Bestandsaufnahme - Kałasznik, Marcelina; Szczęk, Joanna (2022)
For some time now, a clear turn towards education in the field of specialized languages has been observed in education at German studies institutes in Poland. This trend is considered welcome by students and candidates for German studies. Students see it as the practical dimension of the knowledge acquired during their studies. However, whether their needs in the field of specialized language education are fully satisfied is the question to be examined in this paper. Study programmes in German Studies at Polish universities with a focus on specialized language training will be analyzed. The focus will be on the content components of the study programmes offered. The aim of the analysis is to diagnose the current situation and uncover desiderata in this area.
Keywords: Business German; University Education in Poland; German Studies; specialised languages; study programmes